Shem Pete's Alaska : The Territory of the Upper Cook Inlet Dena'ina - Alex, Daniel; Pete, Shem, approximately 1896-1989; Fall, James A.; Kari, James M. (Book collections on Project MUSE., 2016)
"Shem Pete (1896-1989), the colorful and brilliant raconteur from Susitna Station, Alaska left a rich legacy of knowledge about the Upper Cook Inlet Dena'ina world. Shem was one of the most versatile storytellers and historians in twentieth century Alaska. His lifetime travel map of approximately 13,500 square miles is one of the largest ever documented in this degree of detail anywhere in the world. Reflecting the latest scholarship on Upper Inlet Dena'ina ethnogeography and history, this revised second edition includes new place names, two new essays, numerous annotations, and new photographs. It also illustrates how Shem Pete's Alaska has contributed to the recognition of the Dena'ina heritage of southcentral Alaska since the publication of the second edition in 2003. The names form a reconstructed place name network from the vantage points of the life experiences of Shem Pete and other Dena'ina and Ahtna speakers. The place names are annotated with comments and stories by Shem Pete and more than fifty other contributors, and with historic references, vignettes, numerous photographs, a selection of historic maps, and shaded-relief place name maps. The authors provide perspective on Dena'ina language and culture, and a summary of Dena'ina geographic knowledge and place name research methodology. The book is a significant contribution to Athabascan ethnography and linguistics, the history of Alaska, and to the fields of ethnogeography and onomastics. This book will be the basic reference work on the Dena'ina people of Upper Cook Inlet"--Provided by publisher.